Nursing practice and health care - Hinchliff, Sue ;Norman, Sue ;Schober, Jane (London, United Kingdom : Arnold, 2003)
Suitable for those studying nursing at degree and diploma level, and for students on post-registration courses, conversion courses, or those returning to practice. This book provides support for the student to develop skills in critical thinking to enable the development of an accountable, professional practitioner.
Chapter 1: Nursing today and tomorrow- Jane Salvage -- Chapter 2: Principles of professional practice- Norma Fryer -- Chapter 3: Maintaining professional standards- Susan Savage -- Chapter 4: Ethical dimensions of practice- Paul Gibbons -- Chapter 5: Nurse-patient relationships- Katrina Neal -- Chapter 6: Assessment: the foundations of good practice- Ruth Beretta -- Chapter 7: Evidence-based practice- Alison Loftus-Hills, Elizabeth McInnes and Yana Richens -- Chapter 8: Care delivery: the needs of children- Catherine Lawrence, Faith Gibson and Judy Zur -- Chapter 9: Care Delivery: the needs of young people- Marcelle de Sousa -- Chapter 10: Care Delivery: the needs of the mature adult- Jackie Elton -- Chapter 11: Care delivery: the needs of older people- Jackie Elton and Jane Valente -- Chapter 12: A relationship-centred approach to working with older people and their families- Sue Davies and Mike Nolan -- Chapter 13: Coping with expected and unexpected death- Kieron Thayre and Ian Peate -- Chapter 14: Quality in health care- Alison Norman and Jane Brown -- Chapter 15: Managing risk in a health care organization- Sally M Taber -- Chapter 16: Working within a health care team- Nigel Northcott -- Chapter 17: Supporting practitioners in giving high quality care- John Fowler -- Chapter 18: Maintaining a licence to practise: your career as a professional nurse- Jane Schober -- Chapter 19: Consultancy: the future for nursing roles?- Nicky Hayes
Includes bibliographical references and index.
Keywords: NURSING